2017
DOI: 10.3892/br.2017.980
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of the aerobic glycolysis inhibitor dichloroacetate and of the Krebs cycle inhibitor LW6 on cellular and humoral alloimmunity

Abstract: Abstract. Cell metabolism is altered during T-cell and B-cell activation and differentiation. Clarifying the exact metabolic shifts may lead to the development of new immunosuppressive medications. In this study, the effect of the aerobic glycolysis inhibitor dichloroacetate (DCA) and of the Krebs cycle enzyme malate dehydrogenase 2 (MDH2) inhibitor LW6 on T-cell alloimmune clonal expansion and on alloantibody production, was evaluated. T-cell clonal expansion was assessed in two-way mixed lymphocyte reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These effects of DCA on T-cell differentiation are believed to be dependent on reactive oxygen species (ROS) production. 49 51 Recent studies have reported that inhibition of succinate dehydrogenase (a vital enzyme in the TCA cycle) significantly impaired proliferation and neutralization of mitochondrial membrane potential and yielded a decrease in cytokine secretion like IFN-γ, which are all integral parts of T cell functionality. 52 , 53 In addition, DCA suppressed macrophage migration by inhibiting glycolytic reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…These effects of DCA on T-cell differentiation are believed to be dependent on reactive oxygen species (ROS) production. 49 51 Recent studies have reported that inhibition of succinate dehydrogenase (a vital enzyme in the TCA cycle) significantly impaired proliferation and neutralization of mitochondrial membrane potential and yielded a decrease in cytokine secretion like IFN-γ, which are all integral parts of T cell functionality. 52 , 53 In addition, DCA suppressed macrophage migration by inhibiting glycolytic reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that the inhibition of autophagic flux is the only way that LW6 increases the sensitivity to gemcitabine. Regulating other processes, such as tumor immunity [6] and cell metabolism [34], [35], by LW6 might also enhance the anti-cancer effects of gemcitabine [36]. Thus, it was worth to evaluate the anti-cancer effect of LW6 and LW6 plus gemcitabine in vivo since inhibition of several pathways might be superior to an inhibition of only autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…To ascertain whether MDH2 can be a pharmacological target of DIF-1, we needed to determine whether MDH2 inhibition by DIF-1 inhibits cell proliferation and/or promotes glucose uptake, or has no effect on these functions. We thus compared the effects of DIF-1 and the MDH2 inhibitor LW6 [24][25][26][27][28] on the growth of HeLa cells and 3T3-L1 cells in vitro (Figure 4A-D). In both HeLa and 3T3-L1 cells, DIF-1 at 10-40 µM dose-dependently suppressed cell growth (Figure 4A,C), as described previously [16].…”
Section: Effects Of An Mdh2 Inhibitor On the Growth Of Hela And 3t3-l...mentioning
confidence: 99%